25‐4: Late‐News Paper: Xerographic MicroAssembly Printer for LEDs and Beyond. Issue 1 (29th May 2019) - Chow, Eugene M.; Lu, Jeng Ping; Rupp, Bradley B.; Plochowietz, Anne; Crawford, Lara S.; Shreve, Matthew; Raychaudhuri, Sourobh; Butylkov, Sergey; Wang, Yunda; Mei, Ping; Kor, Siv; Wang, Qian; et al.
Abstract : We are building a deterministic massively parallel sorting, assembly and transfer system for microLEDs and other applications. It uses programmable directed electrostatic assembly and transfer (stamp or roller). Small chips (10 um – 500 um), fine registration (<1um, <1°), heterogeneity, and 162 chiplet prints over an inch are demonstrated.